Pengaruh Social Media Usage Terhadap Green Purchase Intention Dendan Attitude, Perceived Behavioral Control, dan Subjective Norms Sebagai Variabel Mediasi Pada Produk Sepeda Listrik - Geryan Setyawan; Soepatini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the impact of social media use on the intention to purchase eco-friendly products, particularly electric bicycles, through the application of the Theory of Planned Behavior (TPB) as the research framework. The factors analyzed encompass attitude, subjective norms, and perceived behavioral control as mediators in the impact of social media on purchase intention. This study utilizes a quantitative methodology with an explanatory framework, collecting data via a survey of university students in the Soloraya region who are knowledgeable about electric bicycles. The study's findings demonstrate that social media significantly influences attitude, perceived behavioral control, and subjective standards, subsequently impacting the intention to purchase environmentally friendly products. The analysis indicates that attitude and perceived behavioral control can mediate the influence of social media on purchase intention, although subjective norms do not exert a significant effect. These findings underscore the significant influence of social media in augmenting the intention to acquire ecologically sustainable products, notably electric bicycles, among university students.